2021
DOI: 10.1186/s12943-021-01467-8
|View full text |Cite
|
Sign up to set email alerts
|

Personalized neoantigen vaccine prevents postoperative recurrence in hepatocellular carcinoma patients with vascular invasion

Abstract: Background Clinically, prophylactic anti-recurrence treatments for hepatocellular carcinoma (HCC) patients after radical surgery are extremely limited. Neoantigen based vaccine can generate robust anti-tumor immune response in several solid tumors but whether it could induce anti-tumor immune response in HCC and serve as a safe and effective prophylactic strategy for preventing postoperative HCC recurrence still remain largely unclear. Methods Pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 60 publications
1
39
0
2
Order By: Relevance
“…Recently, personalized targets have provided a mighty impetus for the development of cancer immunotherapy (CIT). Accordingly, precise therapeutic cancer vaccines (TCVs) have offered alternative strategies for prophylactic and therapeutic treatment of cancers by boosting the patient’s immune system to eliminate tumor cells. , Thereinto, neoantigen-based tumor-specific antigen (TSA) cancer vaccines have acted as attractive TCVs for precise CIT due to their high specificity and strong immunogenicity. , This high immunogenicity of neoantigens without pre-existing central tolerance can activate antitumor-specific CD8+T-cells to eliminate tumor cells and control tumor progression. , Furthermore, neoantigen-based CIT has been extensively verified in pre- or clinic applications. However, traditional hybrid injection in the clinic might cause inappropriate temporal control with poor immuno­stimulatory activity, resulting in an inefficient cross-presentation by antigen-presenting cells (APCs). Moreover, T-cell dysfunction caused by tumor immuno­suppressive microenvironment still poses a big challenge for neoantigen-based CIT. Therefore, it is highly desired to explore novel immunotherapy strategies by enhancing immuno­stimulatory activity and reactivating tumor-resident T-cell functions to improve immuno­therapeutic responses.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, personalized targets have provided a mighty impetus for the development of cancer immunotherapy (CIT). Accordingly, precise therapeutic cancer vaccines (TCVs) have offered alternative strategies for prophylactic and therapeutic treatment of cancers by boosting the patient’s immune system to eliminate tumor cells. , Thereinto, neoantigen-based tumor-specific antigen (TSA) cancer vaccines have acted as attractive TCVs for precise CIT due to their high specificity and strong immunogenicity. , This high immunogenicity of neoantigens without pre-existing central tolerance can activate antitumor-specific CD8+T-cells to eliminate tumor cells and control tumor progression. , Furthermore, neoantigen-based CIT has been extensively verified in pre- or clinic applications. However, traditional hybrid injection in the clinic might cause inappropriate temporal control with poor immuno­stimulatory activity, resulting in an inefficient cross-presentation by antigen-presenting cells (APCs). Moreover, T-cell dysfunction caused by tumor immuno­suppressive microenvironment still poses a big challenge for neoantigen-based CIT. Therefore, it is highly desired to explore novel immunotherapy strategies by enhancing immuno­stimulatory activity and reactivating tumor-resident T-cell functions to improve immuno­therapeutic responses.…”
Section: Resultsmentioning
confidence: 99%
“…Transcatheter arterial chemoembolization (TACE) was an effective strategy for preventing recurrence. Cai et al [129] subcutaneously injected neoantigen peptide vaccine into ten patients undergoing radical surgical resection and prophylactic TACE therapy. The median recurrence-free survival of the five patients with responsive neoantigens was considerably longer than those with non-responsive neoantigens or with only the initial vaccine.…”
Section: Monotherapymentioning
confidence: 99%
“…Compared to the high levels of TMB found in skin and lung cancers (hypermutated cancers), or to the lowest levels characteristic of leukemias and pediatric tumors [123], HCC is considered as a low to moderate mutated tumor. Its TMB ranges from 2 to 5 somatic mutations per megabase (Mb), reflecting in approximately 60 non-synonymous mutations within the exomic regions [124][125][126]. HCC mutations are not evenly displayed all over the tumor cell genome; there are mutational hot spots such as CTNNB1, TP53, NBPF1, MUC4, MUC16, ALB, ARID1A, AXIN1, APOB, and ALB [10,72,127].…”
Section: Mutations In Hcc As Elements For Neoag-based Vaccinesmentioning
confidence: 99%
“…Therefore, future strategies should consider the combination of vaccines with immune-stimulating agents and blockade of immune checkpoints to reverse the immunosuppressive environment [129]. A recent vaccination study with personalized neoAgs in 10 HCC patients has demonstrated vaccine safety and immunogenicity, but the low patient number does not allow us to reach solid conclusions on clinical activity [126]. In the same line, and with the aim of improving efficacy, a recent phase I/II clinical trial has assessed the safety of a DNA plasmid-based vaccine encoding patient-specific neoAgs (GNOS-PV02) in combination with IL-12-producing plasmid (INO-9012) and pembrolizumab (PD-1), yielding promising results [138].…”
Section: Mutations In Hcc As Elements For Neoag-based Vaccinesmentioning
confidence: 99%